ICTHYOFAUNAL DIVERSITY OF A WETLAND ECOSYSTEM - SUVI, S.; SHIBU, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2016)
Biodiversity is the variability among living organism of all ecosystem, which is essential for ecosystem stability. The health of the environment decides the diversity and productivity of the system. Wetlands are the most productive ecosystem in the world. This paper documents the diversity of fishes in a wetland ecosystem. The icthyofauna is represented by 21 Species belongs to 7 orders and 13 families and 15 genera. The family Cyprinidae showed maximum individual diversity followed by the order Perciforms with 5 families, each orders Siluriforms, Beloniforms, Mugiliforms. Scorpaeniformes and Tetraodoniiformes with 1 family were noted during the study. However the unscientific fishing, overexploitation, habitat modification, reclamation of paddy fields, domestic wastes and human activities, now the fish fauna of this wetland is under threat. Therefore sustainable management and careful monitoring are to be ensured for the conservation of the rich biodiversity of these wetland ecosystem.